The Implementation MuluMile’s Social Activities Program “I Want to Be” in creating Community Development - Mubarok, Muhammad Luthfi; Koeswandi, Tika Annisa Lestari; Nurfitriya, Mira (Universitas Pendidikan Indonesia, 2021)
The purpose of this research is to explain the implementation MuluMile’s social activities program “I want to be” in creating community development. Development is an issue that is often an important discussion in efforts to increase and equalize the economy. Every element of society should take its role in realizing this, including MuluMile. Therefore, the